Integrated Development of Sports News and Cultural and Creative Industries from the Perspective of Globalization: Opportunities and Challenges of Media Communication Policy - Wang, Shuboyue (International Journal of Social Sciences and Public Administration, 2024)
In this way, from the perspective of globalization, this paper can explore the development trend of the integration of sports news and cultural and creative industries, and deeply analyze the opportunities and difficulties encountered by media communication policies in this process. With the accelerated pace of globalization, sports events, as the key media of cultural transmission, show their irreplaceable importance. Firstly, the paper analyzes the characteristics of sports news in detail, including its communication mechanism, the attributes of target groups, as well as various challenges and opportunities faced in the context of globalization. Then the paper Outlines the core meaning of cultural and creative industry and its innovative development track, and clarifies the cornerstone of the marriage between sports news and cultural and creative industry. Then the paper further discusses the role of sports events in cultural communication, and carefully examines the innovative practice of sports news in the field of cultural and creative industry, as well as the penetration and influence of cultural and creative industry on sports event reporting. In particular, the opportunities and challenges brought by media communication policies to this integrated development are emphasized, and countermeasures are put forward. In summary, the deep integration of sports news and cultural and creative industries not only promotes cultural exchange and identity, but also injects new impetus into economic development and social progress, emphasizing the importance of international cooperation and policy support.